Cherry Angiomas on the Scalp - Kim, Jae-Hong (S. Karger AG, 2009)
Cherry angiomas are a common cutaneous vascular proliferation which manifests as single or multiple spots and occurs predominantly on the upper trunk and arms. They typically appear as round-to-oval, bright, red, dome-shaped papules and pinpoint macules measuring up to several millimeters in diameter. The histopathologic findings of a cherry angioma are consistent with a true capillary hemangioma, which is formed by numerous, newly developed capillaries with narrow lumens and prominent endothelial cells arranged in a lobular fashion in the papillary dermis. Herein, we report a case of multiple cherry angiomas on the scalp, an uncommon location for cherry angiomas.